L’Australie : Le déclin relatif de l’agriculture depuis 1970 - Stent, William (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The present article begins by describing the institutionnal framework of Australian agriculture, recent aspects of evolution in agricultural production, exports, costs and in comes. Ii shows how since 1967 agricultural policy is becoming more and more selective, while at the same time its influence on economic policy is decreasing. This change is attributed to industrialization of the country and to the growing participation of agriculture in the international market. This new form of growth, even less than the old one, cannot solve the issue of rural poverty in Australia nor that of hunger in the world.